Effect of astragalus injection on left ventricular remodeling in HFmrEF: a systematic review and meta-analysis - Han, Xu; Huang, Lumei; Li, Geng; Mou, Xinglang; Cheng, Caihong (Frontiers in Cardiovascular Medicine, 2024)
Objectives The aim of this meta-analysis is to evaluate the effect of astragalus injection (AI) on left ventricular remodeling (LVR) in patients with heart failure with mildly reduced ejection fraction (HFmrEF). Methods The randomized controlled trials (RCTs) of AI in treating HFmrEF were retrieved from 8 major English and Chinese electronic databases, up until November 30, 2023. To evaluate the methodological quality of the included studies, the Cochrane bias risk tool and the Modified Jadad Scale were employed. Stata 17.0 software was utilized for statistical analysis, sensitivity analysis, and assessment of publication bias. Results Ten RCTs with 995 patients (562 males and 433 females) were identified. Meta-analysis indicated that compared to conventional treatment (CT), AI significantly improved LVR, specifically increasing left ventricular ejection fraction (LVEF, MD = 4.56, 95% CI: 3.68–5.44, p < 0.00001), decreasing left ventricular end-diastolic volume (LVEDV, MD = −7.89, 95% CI: −11.13 to −4.64, p < 0.00001), left ventricular end-diastolic diameter (LVEDD, MD = −4.18, 95% CI: −5.79 to −2.56, p < 0.00001), left ventricular end-systolic volume (LVESV, MD = −8.11, 95% CI: −11.79 to −4.43, p < 0.00001), and left ventricular end-systolic diameter (LVESD, MD = −3.42, 95% CI: −4.90 to −1.93, p < 0.00001). AI also improved clinical efficacy (RR = 4.62, 95% CI: 3.11–6.88, p < 0.00001), reduced N-terminal pro-brain natriuretic peptide (NT-pro BNP, MD = −27.94, 95% CI: −43.3 to −12.36) level, without increasing the incidence of adverse reactions (RR = 1.60, 95% CI: 0.59–4.29, p = 0.35). Sensitivity analysis confirmed the reliability of the merged results, and Begg's and Egger's tests showed no significant publication bias. Conclusion The systematic review and meta-analysis revealed that combining AI with CT improves LVR without increasing adverse events in HFmrEF patients. However, caution is needed in interpreting the results due to limited evidence. Future high-quality RCTs are needed to support these conclusions. Systematic Review Registration https://www.crd.york.ac.uk/prospero/, PROSPERO [CRD42022347248].